2021
DOI: 10.1186/s12199-021-00966-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the link between blood cobalt concentrations and insulin resistance in adults without diabetes

Abstract: Background Little is known about the effects of environmental cobalt exposure on insulin resistance (IR) in the general adult population. We investigated the association between cobalt concentration and IR. Methods A total of 1281 subjects aged more than 20 years with complete blood cobalt data were identified from the National Health and Nutrition Examination Survey (NHANES) 2015–2016 cycle. Blood cobalt levels were analyzed for their association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Interestingly, we observed a positive association between elevated urinary Co and prevalence of T2D. Previous population-based studies on the association between Co and T2D have not been consistent, and the results might differ according to the types of specimens [45,46]. Additionally, exposure to heavy metals may negatively affect kidney function, which may bias the associations between urinary metals and prevalence of diabetes in cross-sectional studies.…”
Section: Discussioncontrasting
confidence: 50%
“…Interestingly, we observed a positive association between elevated urinary Co and prevalence of T2D. Previous population-based studies on the association between Co and T2D have not been consistent, and the results might differ according to the types of specimens [45,46]. Additionally, exposure to heavy metals may negatively affect kidney function, which may bias the associations between urinary metals and prevalence of diabetes in cross-sectional studies.…”
Section: Discussioncontrasting
confidence: 50%
“…On the contrary, in 47,595 women participating in the Sister Study, hypertension risk was associated with higher residential exposure to Co (33). In the NHANES cohort, urinary Co was negatively correlated with obesity in children/ adolescents (34) and with HOMA-IR in female adults (35) in the NHANES cohort. Hu et al (36) found that participants with higher urinary Co had a higher prevalence of obesity, insulin resistance, higher WC, and triglycerides, and lower HDL.…”
Section: Discussionmentioning
confidence: 87%
“…and Chen et al . found that female adults had higher Co levels than male adults [ 35 , 36 ]. However, this study showed that men were more likely than women to accumulate Co in the body.…”
Section: Discussionmentioning
confidence: 99%